Population genetics of self-incompatibility in a clade of relict cliff-dwelling plant species. (18th August 2015) - Silva, Jose L.; Brennan, Adrian C.; Mejías, José A.
Abstract : This study highlights the value of performing detailed mating system studies in plant species of high conservation value, such as the rare and relict species of Sonchus section Pustulati described here. This study adds to the evidence that outcrossing mating systems based on SSI are highly resilient even under long-term conditions of small, fragmented, and isolated populations, possibly due to mating system flexibility with the presence of some selfing and the fact that high cross-compatibility is achieved for relatively modest dominantly expressed S allele polymorphism. We highlight the importance of taking mating system factors into account as part of conservation efforts. Abstract: The mating systems of species in small or fragmented populations impact upon their persistence. Small self-incompatible (SI) populations risk losing S allele diversity, responsible for the SI response, by drift thereby limiting mate availability and leading to population decline or SI system breakdown. But populations of relict and/or endemic species have resisted these demographic conditions over long periods suggesting their mating systems have adapted. To address a lack of empirical data on this topic, we studied the SI systems of three relict cliff-dwelling species of Sonchus section Pustulati (Asteraceae): S. masguindalii, S. fragilis and S. pustulatus in the western Mediterranean region. We performed controlled pollinations within and between individuals to measure index of SI (ISI) expression and identify S alleles in multiple population samples. Sonchus masguindalii and S. pustulatus showed strong SI (ISI = 0.6–1.0) compared to S. fragilis (ISI = 0.1–0.7). Just five S alleles were estimated for Spanish S. pustulatus and a moderate 11-15 S alleles for Moroccan S. pustulatus and S. fragilis, respectively. The fact that autonomous fruit set was generally improved by active self-pollination in self-compatible S. fragilis suggests that individuals with weak SI can show a wide range of outcrossing levels dependent on the degree of self or outcross pollen that pollinators bear. We conclude that frequent S allele dominance interactions that mask the incompatibility interactions of recessive S alleles leading to higher mate availability and partial breakdown of SI leading to mixed mating, both contribute to reproductive resilience in this group.